Patients with Minor Non-Disabling Stroke (MiNDS): results of a structured cardiovascular rehabilitation program. (11th May 2022) - Palermi, S; Brugin, E; Compagno, S; Pescatore, V; Tegon, G; Sarto, M; Marin, R; Masato, M; Panico, A; Biffi, A; Giada, F
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Ischemic cerebral and cardiac events are the leading causes of mortality and morbidity in Minor non-Disabling Stroke (MiNDS) patients. Control of cardiovascular risk factors, including physical activity levels, is a key strategy in secondary prevention of MiNDS. However, there is a gap between recommendations and real achieved physical activity levels in these patients. Clinical benefits obtained with cardiovascular rehabilitation in cardiac ischemic patients could be obtained with similar programs also in patients with MiNDS, given the common pathophysiological substrate of these two diseases. Purpose: To evaluate safety, effectiveness and feasibility of a cardiovascular rehabilitation program based on structured physical exercise (SPE) in patients with MiNDS. Methods: 39 MiNDS patients (26 males, mean age 66 years) underwent an accurate medical screening process, body composition evaluation, cardiopulmonary exercise test (CPET) and muscular strength assessment, before and after a 12-sessions in-hospital SPE program, and after 6- and 12-months follow-up during which they could continue their training schedule on their own. Results: After in-hospital rehabilitation program, a significant improvement in CPET parameters, body composition and muscular strength was observed. These modifications persisted in the 32 patients who continued 6- and 12- months follow-up training, while regressed in the 7 patients who stopped training. Conclusions: Results of the present study show that a SPE-based cardiovascular rehabilitation program provides clinical benefit in patients with MiNDS.